Bionomy of the laurel scale Aonidia lauri (Bouche) (Hemiptera: Diaspididae) in Podgorica, Montenegro - Graora, Draga Đ; Radonjić, Sanja (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Aonidia lauri (Bouche) (Hemiptera: Diaspididae) is a serious pest of laurel (Laurus nobilisL.) in urban parts of the City of Podgorica (Montenegro). Severe infestation causes chlorotic spots and necrotic rings around feeding spots, drying and dieback of leaves and buds. In addition, plants become physiologically weak and lose in aesthetic quality, while continuous infestation in urban areas often leads to partial or complete drying of plants.This study of the biology of A. lauri on L. nobilis was carried out at three locations in Podgorica (’Stara Varoš’, ’Centar’ and ’Preko Morače’), Montenegro, in 2010 and 2011. A. lauri developed three generations annually and overwintered on laurel leaves and branches as the second-instar nymph-larval stage. An extended period of larval development ensures a continuous presence of all development stages on plants, which leads to overlapping of generations.Sporadic predatory ladybirds, Chilocorus bipustulatus (L.) (Coleoptera: Coccinellidae), whose larvae and adults feed on scales, were detected inside A. lauri colonies.
Keywords: Laurel scale; Bionomy; Predators; Montenegro